2011
DOI: 10.1038/nature10143
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ubiquitin-like protein Hub1 in splice-site usage and alternative splicing

Abstract: Alternative splicing of pre-messenger RNAs diversifies gene products in eukaryotes and is guided by factors that enable spliceosomes to recognize particular splice sites. Here we report that alternative splicing of Saccharomyces cerevisiae SRC1 pre-mRNA is promoted by the conserved ubiquitin-like protein Hub1. Structural and biochemical data show that Hub1 binds non-covalently to a conserved element termed HIND, which is present in the spliceosomal protein Snu66 in yeast and mammals, and Prp38 in plants. Hub1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(176 citation statements)
references
References 44 publications
14
162
0
Order By: Relevance
“…However, an analysis of the 5Јss hexamer for the occurrence of consensus versus non-consensus nucleotides (log odd score analysis) suggests that a statistically significant proportion of N3 nucleotides are non-consensus in our SpPrp18-dependent intron data set (data not shown). Introns with weak/ abnormal splice sites can have greater dependence on splicing factors, as reported even in budding yeast (47,48). Also, it is suggested that the splicing apparatus is limiting, and thus different cellular transcripts encounter inherent competition for these splicing factors (49).…”
Section: Discussionmentioning
confidence: 91%
“…However, an analysis of the 5Јss hexamer for the occurrence of consensus versus non-consensus nucleotides (log odd score analysis) suggests that a statistically significant proportion of N3 nucleotides are non-consensus in our SpPrp18-dependent intron data set (data not shown). Introns with weak/ abnormal splice sites can have greater dependence on splicing factors, as reported even in budding yeast (47,48). Also, it is suggested that the splicing apparatus is limiting, and thus different cellular transcripts encounter inherent competition for these splicing factors (49).…”
Section: Discussionmentioning
confidence: 91%
“…(C) Quantitative RT-PCR showing accumulation of long and short GFP transcripts in the indicated genotypes. Stably expressed At5g60390 was used for normalization (Wang et al 2014). acetylation, methylation, and phosphorylation, ubiquitination is increasingly recognized for its role in regulating the spliceosomal cycle (Bellare et al 2008;Song et al 2010;Mishra et al 2011;Korneta et al 2012;Ammon et al 2014;Chen and Moore 2014;Oka et al 2014). Notably, PRP8, which can bind ubiquitin through its conserved JAMM (JAB1/MPN/Mov34 metalloenzyme) domain, was detected as an ubiquitin conjugate in affinity-purified particles in budding yeast, suggesting a means to reversibly modulate the activity of this protein (Bellare et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitin-proteasome pathway is the key mechanism for proteolysis that has been implicated in protein folding, cell cycle progression, and apoptosis (17). This complex and tightly controlled pathway has the capacity to precisely regulate the timing of protein degradation during the cell cycle or after exposure to specific external stimuli and is implicated in epigenetic regulation (18), including histone methylation (19). Spliceosome, splicing factors, and DNA methylation.…”
Section: Critical Metabolic Network In Apis Are Enriched In Methylatedmentioning
confidence: 99%